Aflibercept as Adjunctive Treatment for Filtration Surgery in Neovascular Glaucoma - Kitnarong N. (2023)
Objective: To investigate intravitreal aflibercept (IVA) injection as an adjunctive treatment to trabeculectomy with mitomycin C (TMC) and panretinal photocoagulation (PRP) for neovascular glaucoma (NVG). Materials and Methods: PRP and IVA (2 mg/0.05 ml) injection were given, and TMC was performed within 2 weeks after IVA. Additional PRP, laser suture lysis, subconjunctival 5-fluorouracil injection, and bleb needling were performed after TMC if indicated. Best corrected visual acuity (BCVA), intraocular pressure (IOP), surgical complications, and number of anti-glaucoma medications were collected. Results: Five eyes from 5 consecutive patients were included. Two eyes had proliferative diabetic retinopathy (PDR), 2 central retinal vein occlusion, and 1 ocular ischemic syndrome (OIS) (mean initial IOP: 46.8±6.8 mmHg). NVI regression occurred in one eye after PRP alone, and in one eye after PRP and IVA resulting in a good IOP control with topical medical therapy. The other 3 underwent TMC. The preoperative IOP was 34 (OIS), 54 (PDR), and 50 (PDR) mmHg. The 3-month postoperative IOP decreased to 8, 8, and 4 mmHg, respectively, and to 21, 10, and 6 mmHg, respectively, at the last visit. Only the one OIS eye required postoperative topical IOP-lowering medications. Final BCVA was improved, unchanged, and decreased in 2, 2, and 1 eye, respectively. No intraoperative/postoperative complications or NVI recurrence were observed (mean follow-up: 10.7 months). Conclusion: Intravitreal aflibercept was shown to be a potentially effective additional treatment to PRP and TMC in patients with NVG.